Faecal bile acids and clostridia in the aetiology of colorectal cancer. - Murray, W. R. (Nature Publishing Group, 1980)
This study was undertaken in an attempt to confirm the increased bile-acid concentration in association with nuclear dehydrogenating Clostridia (NDC) in the faeces of colorectal cancer patients. We have studied 37 patients with colorectal cancer and 36 control patients with no known gastrointestinal disease. Stool specimens were obtained for biochemical analysis (total faecal bile acid (FBA), lithocholic deoxycholic and cholic acids) and NDC isolation. The mean total FBA concentration (mumol/g) in the control group was 20.5 +/- 2.2 (s.e.) significantly higher (P < 0.001) than the colorectal-cancer group (11.8 +/- 0.7). There was no statistically significant difference in the percentage distribution of the individual FBAs measured. NDC were isolated from the faeces of 64% of colorectal-cancer patients and 15% of control patients, this difference being statistically significant (P < 0.001). These results suggest that bacteria capable of metabolizing steroids may be implicated in the aetiology of colorectal cancer. However, the relationship between FBA and colorectal cancer requires further evaluation.